Working Adaptation - Damidavičius, Matas (Problemos, 1976)
The author tries to define and reveal the contents of such concepts as professional adaptation, working adaptation, socialization and to show the difference and interrelation of the social processes which convey these concepts. Objective and subjective criteria, indices and factors of working adaptation are also discussed. Working adaptation is understood as the adaptation process of a worker to some job under certain working conditions and adaption of the relationships and behaviour patterns existing in a working people’s collective. A system of empirical indicators is suggested to serve as criteria of working adaptation. It allows to apply these criteria to a concrete sociological investigation of workers’ adaptation to work.